Antibiofilm and Antimicrobial Effectiveness of Chlorhexidine Hexametaphosphate Nanoparticles as a Coating for Orthodontic Miniscrews - Selma Merza Hasan, Akram Faisal Alhuwaizi (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Inflammation around miniscrews can be responsible for about 30% of failures of these devices that associated with miniscrews insertion transgingivally, which straightly accessible to all forms of microorganisms existing in the oral cavity. Chlorhexidine hexametaphosphate has been described as a material that offers persistent, slow release of active chlorhexidine over time when nacked to an aqueous conditions. Aims of study: To test the antibiofilm and antimicrobial effects of OMS coated with antimicrobial nanoparticle (Chlorhexidine hexametaphosphate). Materials and Methods: The sanitized orthodontic minisecrews coated by nanoparticles, to establish the effectiveness of nanoparticles against formation of biofilm for S. mutans, A. actinomycetemcomitans and C. albicans. The agar method was used to evaluate the antimicrobial validity of the nanoparticles coated OMS. Gram-positive bacteria including S. mutans and S. gordonii gram negative like A. actinomycetemcomitans, p. gingivalis and Candida were used to test the antimicrobial activity of the titanium and stainless steel coated orthodontic miniscrews. After incubation for 24 hours at 37℃, the agar plates were distant from the incubator and the zone of inhibition was examined for each OMS in mm using a ruler around each disc. The zone of inhibition was measured in terms of length (mm), breadth (mm), and area (mm2) due to linear shape of samples. Area of the ellipse was calculated as π (l/2 × b/2). Results: The inhibition areas around stainless steel coated orthodontic miniscrews were larger than those around the titanium ones for all types of microorganisms. It were statistically significant for S. mutans and A. Actinomycetumcomitance but not significance for S. Gordonii, P. gingivalis and candida. The inhibition areas for all bacteria were comparable but notably larger than that for candida. Chlorohexidine hexametaphosphate nanoparticles exhibited powerful antibiofilm activity against the selected S. mutans, A. Actinomycetumcomitance and candida. Conclusion: This study revealed that OMS coated by CXH-HMP nanoparticles as antimicrobial agent can provide significant antimicrobial activity that inhibit bacterial growth and aid in biofilm reduction.